2006
DOI: 10.1007/s00360-006-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid profile and myocardial superoxide dismutase in swim-trained young and middle-aged rats: comparison between left and right ventricular adaptations to oxidative stress

Abstract: Region-wise interactive effects of age, swim intensity, and duration on exercise performance in the myocardium and serum lipid profile in young (4 months) and middle-aged (12 months) rats were examined. Animals were allocated to the sedentary control (SE-C) or one of the nine trainee groups. Swim training was for 6 days/week and for 4 weeks at 3 durations (20, 40, and 60 min/day) and intensities (2%, low; 3%, medium; 5%, high). Swim velocity and external work showed an age-related decline with low-intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
3
6
1
1
Order By: Relevance
“…A significant increase in the levels of MDA has been observed from juvenile to adult groups and which in part agrees with findings of Corriea et al (2003) and Ravi Kiran et al (2006) in invertebrates and vertebrates. A negative correlation has been observed, with increasing MDA levels and decreasing SOD activities, in all the earthworm age groups.…”
Section: Discussionsupporting
confidence: 91%
“…A significant increase in the levels of MDA has been observed from juvenile to adult groups and which in part agrees with findings of Corriea et al (2003) and Ravi Kiran et al (2006) in invertebrates and vertebrates. A negative correlation has been observed, with increasing MDA levels and decreasing SOD activities, in all the earthworm age groups.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it reduces lipid peroxidation in the gastrocnemius muscle and in the heart (p < 0.01). Although acute exhaustive or chronic exercise increases oxidative stress (25), our findings support the idea that the chronic exercise has beneficial effects in improving metabolic adaptation and maintaining oxidant balance (37,42,44). The serum lactate levels were not examined in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Because the exhausting swimming exercise does not cause oxidative stress, this protocol might not be considered as sufficiently exhausting. However, the moderate training protocol applied in this study (5% overload, 60 min/day-5 days/week) is considered as highly intensive according to Ravi Kiran et al (37). We also found that probiotic intake during exercise led to a reduction in lipid peroxidation of the liver, whereas it led to an increase in antioxidant enzymes such as SOD and/or CAT in the colon and in the heart.…”
Section: Discussionsupporting
confidence: 54%
“…Other authors have also reported that swimming training stabilizes body weight in rats [52], [53]. According to Ravi Kiran et al [52], who investigated different training intensities and durations in 4 and 12 months-old rats, the training protocol intensity applied in our study can be considered as high intensity (5% overload, 60 min/day –5 days/week). A high intensity swimming protocol demands high energy matching capacities so as to overcome the task.…”
Section: Discussionmentioning
confidence: 82%